The Relationship of Complex Post-traumatic Stress Disorder and Post-traumatic Stress Disorder in a Culturally Distinct, Conflict-Affected Population: A Study among West Papuan Refugees Displaced to Papua New Guinea - Silove, Derrick; Tay, Alvin Kuowei; Kareth, Moses; Rees, Susan (Frontiers in Psychiatry, 2017)
Background Controversy continues about the validity of the construct of complex posttraumatic stress disorder (C-PTSD). In particular, questions remain whether C-PTSD can be differentiated from PTSD and, secondarily, other common mental disorders. The examination of these issues needs to be expanded to populations of diverse cultural backgrounds exposed to prolonged persecution. We undertake such an inquiry amongst a community sample of West Papuan refugees exposed to extensive persecution and trauma. Methods We interviewed over 300 West Papuan refugees using the Refugee Mental Health Assessment Package (R-MHAP) to record symptoms of PTSD, C-PTSD, major depressive disorder (MDD) and complex grief (CG). We used first and second order confirmatory factor analysis to test aspects of the convergent and discriminant validity of C-PTSD. Results The CFA analysis supported both a one-factor and two-factor model of PTSD and C-PTSD. Nested model comparison tests provide support for the parsimonious one-factor model solution. A second order CFA model of PTSD and C-PTSD produced a poor fit. The modified three-factor multi-disorder solution combining a traumatic stress factor (amalgamating PTSD and C-PTSD), MDD and CG yielded a good fit only after removing three CG domains (estrangement, yearning, and behavioural change), a model that produced large standardized residuals (>.20). Conclusions The most parsimonious model yielded a single traumatic stress factor combining symptom domains of C-PTSD and PTSD in this culturally distinct community exposed to extensive persecution and conflict-related trauma. There may be grounds for expanding the scope of psychological treatments for refugees to encompass this wider traumatic stress response. Our findings are consistent with theoretical frameworks focusing on the wider traumatic stress reaction of refugees exposed to human rights-related traumas of mass conflict, persecution and displacement.